2016
DOI: 10.1371/journal.pntd.0004920
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Rabies Virus-Neutralizing Antibodies after Vaccination of Rural Population following Vampire Bat Rabies Outbreak in Brazil

Abstract: BackgroundAnimal control measures in Latin America have decreased the incidence of urban human rabies transmitted by dogs and cats; currently most cases of human rabies are transmitted by bats. In 2004–2005, rabies outbreaks in populations living in rural Brazil prompted widespread vaccination of exposed and at-risk populations. More than 3,500 inhabitants of Augusto Correa (Pará State) received either post-exposure (PEP) or pre-exposure (PrEP) prophylaxis. This study evaluated the persistence of rabies virus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Inadequate antibody titers were independently associated with male sex at birth in the present study. This result is consistent with the findings of several other studies that reported higher antibody titers after rabies PrEP or postexposure prophylaxis in females [ 11 , 12 , 14 , 15 ]. A stronger postvaccination antibody response in females has been evidenced with other vaccines such as hepatitis A, hepatitis B, rubella, diphtheria, tetanus, and brucella [ 16 ], whereas the response was stronger in males for other vaccines such as pneumococcal, meningococcal vaccines, measles, and yellow fever.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Inadequate antibody titers were independently associated with male sex at birth in the present study. This result is consistent with the findings of several other studies that reported higher antibody titers after rabies PrEP or postexposure prophylaxis in females [ 11 , 12 , 14 , 15 ]. A stronger postvaccination antibody response in females has been evidenced with other vaccines such as hepatitis A, hepatitis B, rubella, diphtheria, tetanus, and brucella [ 16 ], whereas the response was stronger in males for other vaccines such as pneumococcal, meningococcal vaccines, measles, and yellow fever.…”
Section: Discussionsupporting
confidence: 93%
“…Several authors have shown that both higher seroconversion rates and higher antibody titers were observed in younger age groups [ 15 , 19 , 20 ]. However, no statistical association between age at PrEP and immune response was evidenced in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the limited number of female subjects, there was little statistical power to detect gender-related association. While other authors also found no relation between age or gender and immune response [10], some have reported gender-and age-related differences in seroconversion rates, GMTs and RVNA persistence in rabies 3 1 ID and 2 2 ID pre-exposure schedules [11,12,14,20,21]. Females were found to have higher antibody levels than males after a 2 2 ID [11] and after a 3 1 ID PrEP schedule [14].…”
Section: Discussionmentioning
confidence: 92%
“…Finally, enteric infection represents a significantly different tissue than the respiratory tract in terms of disease and adaptive immunity; thus, virus tropism differences between species and tissues may also contribute to limiting disease in bats. Similarly, while recent work has shown intact elements of adaptive immunity in bat species [ 17 , 18 , 19 ], the enteric location may generate a dampened adaptive response that permits viral maintenance similar to the members of the microbiome in humans [ 20 ]. Together, these factors likely work in combination and indicate how diverse pools of CoV quasi-species can survive in bat populations.…”
Section: Bats Reservoirs: Shaping Virus Emergencementioning
confidence: 99%